From Ant Trails to Pedestrian Dynamics - Andreas Schadschneider; Ansgar Kirchner; Katsuhiro Nishinari (Applied Bionics and Biomechanics)
This paper presents a model for the simulation of pedestrian dynamics inspired by the behaviour of ants in ant trails. Ants communicate by producing a pheromone that can be smelled by other ants. In this model, pedestrians produce a virtual pheromone that influences the motion of others. In this way all interactions are strictly local, and so even large crowds can be simulated very efficiently. Nevertheless, the model is able to reproduce the collective effects observed empirically, eg the formation of lanes in counterflow. As an application, we reproduce a surprising result found in experiments of evacuation from an aircraft.